The Link Between the Madden‐Julian Oscillation and Rainfall Trends in Northwest Australia. Issue 8 (18th April 2023) - Borowiak, Alexander; King, Andrew; Lane, Todd
Abstract: Rainfall during the monsoon in northwest Australia has increased since the 1950s. Previous studies have explored possible causes of the rainfall increase; however, the trend has not been fully explained. Understanding the cause of this trend is important for interpreting climate projections and local water‐sensitive services. We explore the role of the Madden‐Julian Oscillation (MJO) in explaining the rainfall increase. The MJO, since 1974, has had a longer duration in phases associated with enhanced rainfall in northwest Australia (Phases 5 and 6) during the monsoon. We show that the rainfall trend in northwest Australia is identified only during MJO phases associated with enhanced rainfall, with a large change in daily rainfall distribution in these phases. The increasing occurrence of these MJO phases explains most of the rainfall increase, as opposed to an increase in daily rainfall independent of MJO phase, albeit with some sensitivity to MJO definition. Plain Language Summary: Rainfall during the monsoon in northwest Australia has been increasing since the 1950s. In this study, we explore if a semi‐periodic pulse of rainfall and clouds near the equator, known as the Madden‐Julian Oscillation (MJO), may be related to the increased rainfall in the northwest. This pulse of clouds has been found, since 1974, to be spending longer periods of time over northwest Australia. We observed that the increase in MJO duration over northern Australia leads to increasing rainfall in northwest Australia. Key Points: Rainfall in northwest Australia has been increasing since the 1950s, and the cause of this trend has so far remained unexplained The Madden‐Julian Oscillation (MJO) has also been increasingly occurring in phases associated with increased rainfall over northern Australia The increase in MJO convective phases over northern Australia explains most of the increase in rainfall since 1974 in northwest Australia